(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Soil samples from Yerevan geochemical survey were used for estimation the radioactivity levels due to natural radionuclides (K-40, Th-232, U-238). 52 urban and 8 background soil samples were analysed using gamma spectrometer (CANBERRA). Results sugested a dependence of spatial distribution of natural radionuclides on geological characteristics of Yerevan: in northern part, where volcanic rocks prevail, high levels of radioactivity have been detected, while in the southern parts, rich in sedimentary rocks, low radioactive levels predominate. The radiological hazard caused by the natural radionuclides in soils of Yerevan is insignificant.